Marketability of the College of Business Management and Accountancy (CBMA) Students in LSPU Siniloan Campus - Caramonte, Juliet Acorda (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study presents the marketability of the CBMA students at the LSPU Siniloan campus as they navigate workplace challenges to assess their skills and competencies before graduation and employment by the company or institutions, which is crucial for employment. A research study involved a total of 137 respondents who participated in a survey across three academic programs: BS Accountancy with 48 respondents, BSBA in Financial Management/Marketing Management with 50 respondents, and BS Office Administration with 39 respondents. This study shows that students' interpersonal and personal traits they need to succeed in the profession will depend on their Hard Skills and Soft Skills, respectively. This study used purposive sampling method in selecting participants likely to provide most useful or relevant information for the research question. The majority of students read their courses or materials with comprehension, according to the results. Self-management follows next, in which students can effectively manage their feelings, ideas, and actions in a range of contexts. This research findings shows implications to Curriculum Development which suggests that while core competencies are generally well-developed, discipline-specific strengths can be further leveraged. There are also implications for Career Services on students’ strengths in learning and foundational skills. While on Career services should offer targeted workshops and career mapping sessions that align individual strengths with market demands. Implications for Internship programs should be designed to reinforce classroom learning and bridge skill gaps.